Walkability for utilitarian and leisure purposes: a comparative study on an avenue located in the city of Araçatuba, São Paulo - Crespo, Antonio Arnot Queiroz; Garcia, Ligia Chiesa Fortes; Magagnin, Renata Cardoso (Revista Nacional de Gerenciamento de Cidades, 2022)
More walkable cities contribute to building a sustainable city. In the last decades, the increase in the number of urban displacements carried out by foot highlights the importance of developing methods that seek to analyze the quality of this infrastructure to propose improvements for these users. In this context, this paper aims to present the result of the evaluation of the urban mobility infrastructure destined for walkability for practical and leisure purposes in two areas of an important road axis located in the city of Araçatuba, São Paulo, using the Walkability Index of the Macro and Microscale (in Portuguese the acronym ICMME), proposed by Pires (2018). The methodology allows the evaluation of sidewalks and road intersections based on indicators associated with Safety, Security, Comfort, and Attractiveness. The results show that the sidewalks and intersections located in area 2, intended for leisure walking, offer greater Safety, Security, Comfort, and Attractiveness to users. On the other hand, the sidewalks and crossings of area 1, which are used by people predominantly for displacements with utilitarian purposes (study, shopping, and work) are of lower spatial quality, especially in relation to elements associated with Safety and Security (of the sidewalks) and Safety and Comfort (of the intersections) of users. The results made it possible to identify positive and negative points of the pedestrian infrastructure and can be used to formulate public policies for urban mobility aimed at walkability.